Cultura política e a relação de poder na região de São Mateus: o papel da Câmara Municipal (1848/1889) - Russo, Maria do Carmo de Oliveira (2007)
This work aims to approach, at first, some aspects of the political, social and economical formation of the municipality of São Mateus – a port town in the extreme north of the state of Espírito Santo, Brazil – which used to get and distribute all the agricultural production of the region in the XIX century second half. The raise of the São Mateus Village into the category of a town, in 1848, is the initial marking point, in order to focus political aspects and the formation of a São Mateus’ oligarchy. The here so called oligarchy was centered upon a family of a Colonel and a Major – father and son, respectively – both named Antônio Rodrigues da Cunha, being the son also titled as The Baron of Aimorés. Virtually, all through the imperial era São Mateus was considered the biggest producer of manioc flour in the Espírito Santo province, and one of major importance on the Brazilian coast. Besides, it appeared successfully in the incipient coffee production in that province. The São Mateus River, as a natural route for crops, and its busy port – very close to the shore – where a significant slaves market could be found, favoring the agricultural production, helped promote development to the region. In this scenario, regional peculiarities of the São Mateus River are highlighted, as well as its relation with the sea port of Conceição da Barra – then called Barra de São Mateus. A consecutive analysis is accomplished about the role of its agricultural oligarchy along with the local political power – here represented by the Municipal Lower Chamber – as well as the enlargement of its regional and provincial influences. The regional power relations can be observed through a marriage policy among a same lineage in which a true relatival clan there existed with political influence in the region during the period under study, and thus the formation of a peculiar political culture. The research on the sources has been carried out by consulting the Presidents of the Province’s Reports of that period, available in the State Public Files, some Municipal Lower Chamber’s Records, and the mailing between the municipal and the provincial governments.